2018
DOI: 10.52859/jba.v5i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan E-Filing Oleh Wajib Pajak

Abstract: The purpose of this research is to analyze the influence of perceived usefulness, perceived ease of use, security and privacy, readiness of technology information, user’s satisfaction towards the use of e-Filing. This research uses a primary data. Respondents are the individual taxpayers who report SPT Tahunan using e-Filing and register in the Tax Office (KPP) Madya and Pratama in Tangerang and South Tangerang City. There are 112 respondents in this study. The sampling technique used is convenience sampling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
0
1
1
Order By: Relevance
“…Previous studies on the readiness of information technology for e-Filing usage, as conducted by Andi and Sari (2017), Pu'o et al (2018), and Putra (2019 have affirmed that technology readiness does influence e-Filing adoption. However, this contradicts the findings of Wiratan and Harjanto (2018) which suggest that technological readiness does not impact e-Filing utilization.…”
Section: Introductioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Previous studies on the readiness of information technology for e-Filing usage, as conducted by Andi and Sari (2017), Pu'o et al (2018), and Putra (2019 have affirmed that technology readiness does influence e-Filing adoption. However, this contradicts the findings of Wiratan and Harjanto (2018) which suggest that technological readiness does not impact e-Filing utilization.…”
Section: Introductioncontrasting
confidence: 93%
“…When the system effectively meets user needs, there is potential for continuous and increased utilization of the e-Filing system (Andi & Sari, 2017;Reniati, R et al, 2023). This relationship between perceived satisfaction and e-Filing usage mediated by information technology readiness is also supported by studies conducted by Wiratan and Harjanto (2018) and Maryani (2016). Based on this description, it can be concluded that: H₇: Perceived satisfaction positively influences the use of e-Filing when information technology readiness serves as an intermediary variable.…”
Section: The Effect Of Perceived Satisfaction On E-filing Utilization...supporting
confidence: 74%
“…Dalam (Wiratan & Harjanto, 2018) realisasi penerimaan pajak dapat meningkat pemasukan negara namun tidak melebihi target yang ditetapkan. Hal ini menunjukkan bahwa dibutuhkannya penerimaan pajak yang harus ditingkatkan kembali.…”
Section: A Pendahuluanunclassified